Evaluation of Effective Current Output for Sacrificial Anodes at Various Sea Water Depth - Azami, Adam Hazman (IRC, 2018)
One of the methods that is widely used to prevent corrosion of offshore structure exposed to sea water corrosive environment is the sacrificial anode cathodic protection. The use of corrosion controls are very costly and the effective current output is different for most of the applications. Using ineffective current output in designing sacrificial anodes will increase the corrosion control cost and damage the offshore structure. The objective of this study is to evaluate effective current output of sacrificial anode due to different salinity and dissolved oxygen content and to compare sacrificial anode’s material performance based on various sea water depth. Pure aluminium and aluminium alloy (Al-Zn-Mg-Sn) sacrificial anodes were fabricated and tested in different salinity and dissolved oxygen content following the recommended practice DNV-RP-B401. The result shows that the effective current output for both materials slightly differs at various sea water depth and aluminium alloy sacrificial anodes have better performances than pure aluminium sacrificial anodes. Therefore, the effective current output for sacrificial anodes design can be similar for application of sacrificial anodes at various sea water depth and aluminium alloy is the better material for sacrificial anodes.